The Role of High Sensitivity C-Reactive Protein as an Inflammation Predictor in Cardiovascular Diseases - Cici Nuriah; Iswanti, Febriana Catur; Ariel Pradipta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Inflammation can be measured by analyzing the levels of inflammatory markers, such as High Sensitivity C-reactive Protein (hs-CRP). This protein plays a crucial role as a strong independent predictor indicating the risk of cardiovascular. The hs-CRP can measure the levels of C-reactive protein with high sensitivity, making it a highly responsive marker to acute-phase inflammation. The presence of hs-CRP serves as an inflammation indicator that can predict the potential occurrence of heart attacks, strokes, peripheral artery diseases, and sudden death due to Acute Coronary Syndrome (ACS). Produced by the liver in response to inflammation, hs-CRP is nonspecific and can elevate various types of inflammation, including infections and chronic inflammatory conditions in cardiovascular. This study is a literature review using secondary data from related research. The hs-CRP has a very high sensitivity and specificity level compared to CRP as an inflammation marker. Therefore, hs-CRP serves not only as a diagnostic tool but also as a strong predictor of inflammation, capable of predicting cardiovascular risk.